Clinical and prognostic value of parameters of cytokine regulation in oxygen-dependent patients with the coronavirus disease COVID-19 - O. V. Riabokon; V. V. Cherkaskyi; Yu. Yu. Riabokon; R. O. Shcherbyna (Zaporozhye State Medical University, 2023)
Aim of the work is to find out the clinical and prognostic significance of cytokine regulation parameters in oxygen-dependent patients with COVID-19 coronavirus disease in dynamics of the disease. Material and methods. 78 oxygen-dependent patients with COVID-19 aged from 52 to 84 years were examined. All patients were examined and treated in accordance with the regulations in force at the relevant time. The patients were divided into groups: I group - 38 patients who recovered; II group - 40 patients with fatal outcome of the disease. In the blood serum of patients with COVID-19 and 20 healthy individuals, were determined by enzyme immunoassay the content of interleukin (IL) IL-2 (Elabscience, USA), IL-4 (Affymetrix eBioscience, Austria), IL-6 (Invitrogen, Austria), monocyte chemotactic protein-1 (MCP-1) (Elabscience, USA). Statistical processing was performed in the Statistica 13 for Windows program (StatSoft Inc., No. JPZ804I382130ARCN10-J). Results. The content of IL-2 in the blood serum of oxygen-dependent patients with COVID-19 of both groups was significantly higher (p < 0.001) than in healthy individuals. IL-2 content was higher in patients of II group (p < 0.001) than in patients of I group. In dynamics, a further increase in content of IL-2 was noted in patients of the II group (р < 0.05). The diagnostic significance has been established of the increased level of IL-2 in assessing the high probability of the development of a fatal outcome of the disease during hospitalization (AUC = 0.698, p = 0.030) and in the dynamics of treatment (AUC = 0.745, p = 0.015). The content of IL-6 in the blood serum of oxygen-dependent patients with COVID-19 of both groups was also significantly higher (p < 0.001) than in healthy individuals. However, the level of increase of this cytokine at the time of hospitalization did not have prognostic value regarding the risk of fatal outcome (AUC = 0.539, p = 0.562). In the dynamics of treatment, the content of IL-6 in blood serum continued to increase in patients of the II group (p < 0.01). During this period of observation, a threshold level of increase IL-6 level was established, which indicates a high probability of the development of a fatal outcome in these patients (AUC = 0.850, p < 0.001). The content of chemokine MCP-1 in blood serum at the time of hospitalization in patients of both groups was higher (p < 0.01) than in healthy people. At the same time, the content of MCP-1 in patients of the II group was higher (p < 0.05) than in the patients of the I group. The diagnostic significance of the increased level of MCP-1 was established, which indicated a high probability of the development of a fatal outcome during hospitalization. In dynamics, there was a tendency (p > 0.05) to decrease its content (p > 0.05), however, during this period of observation, MCP-1 did not have prognostic value. IL-4 turned out to be uninformative in prognostic terms for determining the probability of a fatal outcome of COVID-19. Conclusions. Changes in the parameters of cytokine regulation in patients with COVID-19 during the development of oxygen dependence are characterized by a significant increase content of IL-2, IL-6 and chemokine MCP-1 in blood serum. The level of increase of these cytokines has diagnostic value in determining the high probability of the development of a fatal outcome of the disease at certain stages of observation.